Increasing Coffee Productivity Through Farmers Groups Forest Slopes of Subang I Cinongkob Hamlet, Kutaagung Village, Dayeuhluhur District, Cilacap Regency, Central Java - Firdaus, Aef Ridwan; Rahayu, Asri; Nopianto, Dera Trisna; AM, Deratih Fauzy; Sutarman, Frisilla Dwi; Putri Wardani, Jihan Nabilah; Ardiyanto, Mughty; Nuraeni, Neng Melly; Selvia, Popy; Putri Krisnadi, Sri Nur Rizki; Andriana Pratama, Widy; Falah, Miftahul (AbdimasMu UMTAS, 2023)
The main problem faced by farmers is that the productivity of Robusta coffee is still low compared to the productivity potential that can be achieved through good farming management. This research aims to develop a business based on mutual cooperation with other MSME actors. Gunung Leutik coffee and the Subang Slope Forest Farmers Group I collaborated with group 12 UMTAS KKN with the theme "creative economy". This was done to improve and empower farmer groups and also introduce the coffee brand "Gunung Leutik Neglasari" to all corners of the archipelago and even foreign countries. This research was carried out from August to September 2021. It was carried out in Cinongkob Hamlet, Kutaagung Village, Dayeuhluhur District, Cilacap Regency, Central Java.